Analisis Perawatan Alat Bongkar Muat Rubber Tyred Gantry di Terminal Peti Kemas Semarang (TPKS) - Watupongoh, Richard V. B; Rusmiyanto, Dedy (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
This study aims to analyze the reliability and performance of Rubber Tyred Gantry (RTG) cranes using the Mean Time To Repair (MTTR), Mean Time Between Failures (MTBF), and Inherent Availability (IA) methods. The MTTR method is used to measure the average time required for repairs, while MTBF calculates the average time between failures. Meanwhile, the IA method assesses the inherent availability of the equipment based on the previous two parameters. The results indicate that some RTG units experience high MTTR, such as RTG035-12, which recorded a repair time of 124.15 hours in January, and RTG035-13 with 441.23 hours in February. On the other hand, RTG035-19 demonstrated more stable performance with low MTTR in several months. In terms of MTBF, RTG035-16 recorded the lowest value of 0 hours in July, indicating significant disruptions, whereas RTG035-12 exhibited the best performance with the highest MTBF of 614 hours in December. The IA analysis revealed that some RTGs had low values, such as RTG035-13, which only reached 0.312 in February, while RTG035-19 maintained values above 0.95 throughout the year, demonstrating high reliability. This study provides insights into the performance of RTG equipment at the Semarang Container Terminal (TPKS) and emphasizes the need for effective maintenance strategies to enhance operational reliability and efficiency.